Pannexin-1 Contributes to the Apoptosis of Spinal Neurocytes in Spinal Cord Injury - Huang, Yu; Lin, Jin; Chen, Xuanwei; Lin, Jianhua (Frontiers in Physiology, 2021)
Currently, the role of Pannexin-1, a homomeric membrane hemichannel on the neuron cell membrane, in the development of spinal cord injury (SCI) is largely unknown. Herein, we assessed the contribution of Panx1 in the development of SCI. The SCI in vitro model was established using rat primary spinal neurocytes treated with hydrogen peroxide (H2O2). Effects of Panx1 over-expression or depletion in spinal neurocytes were analyzed by lentivirus-mediated transfection of Panx1 and interference sh-Panx1. Decreased cell viability was seen in SCI cells, which was further enhanced under Panx1 over-expression and mitigated by Panx1 deficiency. H2O2 induced an increase of intracellular Ca2+ concentration and upregulated expression of the proapoptotic protein Bax, and apoptosis pathway proteins including cleaved Caspase-3 and PARP1, which was enhanced by Panx1 over-expression or attenuated by Panx1 depletion. On the other hand, H2O2 treatment suppressed the expression of antiapoptotic protein Bcl-2, which was further decreased by Panx1 over-expression or mitigated by Panx1 depletion. The results indicate that Panx1 was involved in the intracellular Ca2+ overload of SCI cells by accelerating extracellular Ca2+ influx, which promoted the apoptosis of spinal neurocytes through Ca2+ dependent pathways, thus aggravating the secondary injury of SCI.